Penerapan Proses Manajemen Risiko Dalam Pengelolaan Keuangan - Widianti, Bernadeta Endang; Yuwono, Minto; Susilowati, Etty (Politeknik Raflesia Press, 2024)
The shopping process cannot be separated from budget planning. The shopping process is strongly influenced by planning instruments. To make budgeting more measurable, a performance-based budgeting system is currently used. Every budget under this system must be created with output in mind. The method used in this paper is a combination of qualitative methods and library research. The aim of this paper is to evaluate various existing theories by comparing them with the available research literature. This paper discusses and analyzes theoretically based on the results of previous research regarding the Role of Risk Management. Based on the results of the discussion, even though the structured arrangement has only been running for 2 years, risk management has been implemented well. The risk map created is also sufficient to explain the possibility and impact of all financial management activities, especially for activities that have a very high level of risk, so that mitigation and follow-up plans can be created quickly. Recommended actions for very high level risks include: guidance and socialization of regulations as well as periodic evaluations to prevent KPA from doubling as PPK, socialization and information about BNT certification and training activities and compliance monitoring to ensure that competent treasurers are in each work unit. It is hoped that these recommendations will improve risk management and help achieve the Ministry's strategic objectives